Engineering the wheat genome to reduce the susceptibility to fungal and viral diseases - Navia Urrutia, Monica (Kansas State University, 2020)
Wheat is a major staple crop, providing calories and proteins to millions of people worldwide. Nevertheless, wheat production is constantly threatened by biotic factors such as pests and diseases, causing about 21% annual yield losses. Undoubtably the use of resistant materials is one of the best strategies to manage diseases, but sources of genetic resistance are limited for some diseases. Genetic engineering is a valuable alternative to incorporate resistance to those diseases for which other management strategies have not been effective. In this research, wheat plants were genetically modified with the aim of reducing susceptibility to three major pathogens Fusarium graminearum (Fusarium head blight - FHB), Magnaporthe oryzae Triticum pathotype (MoT) (wheat blast - WB), and Wheat streak mosaic virus (WSMV). Embryogenic calli of the susceptible cultivar ‘Bobwhite’ were co-transformed via biolistic with DNA plasmids with the purpose of expressing exogenous genes or editing host genes by CRISPR/Cas9. One of the strategies used to enhance resistance to FHB, wheat spike blast (W[subscript]SB) and wheat leaf blast (W[subscript]LB), was to expand the basal defense of wheat by expressing genes encoding antimicrobial peptides (AMPs). Twenty transgenic lines independently transformed with four AMP genes (Ace-AMP1 from onion, WD from wasabi, ARACIN1 from Arabidopsis, and Zeamatin from maize) were challenged with F. graminearum, and four lines, Ace1_8866.A, Wj1_8556.A.4.1, Wj1_8582.A.3, and ARC1_8894.D.1, showed a slight reduction in the percentage of spikelets affected (PSA). Nevertheless the expression of these AMPs did not confer resistance to FHB because the PSAs ranged between 68 and 86%. Significant reductions in the WSB severity (PSA) or WLB severity (% leaf area affected - PLA) were not observed in any of the sixteen lines evaluated. Another approach used in this research to reduce susceptibility to WB was based on the resistance mediated by the host resistance (R) gene – pathogen avirulence (AVR) gene interaction. After assessing the presence of 22 effector genes in 102 South-American MoT isolates, four AVR genes AVR-Piz-t, AVR-Pi9, AVR-Pi54 and ACE1 were found in high frequency. The rice R gene Piz-t was used to transform wheat, and transgenic lines were challenged with MoT isolate T-25. Significant reductions in susceptibility to W[subscript]SB were not detected, but the lines Piz-t_5238.C.1 and Piz-t_5503.C1 showed a significant decrease in PLA, suggesting that Piz-t could confer some resistance to W[subscript]LB. To incorporate resistance to WSMV, the wheat endogenous genes eIF(iso)4E-2 and eIF4G, encoding translation initiation factors which could favor the multiplication of the virus in the host, were CRISPR/Cas9-edited. Four T₀ plants with mutations in the target site were recovered. T₂ plants from edited lines 4385 (six eIF(iso)4E-2 alleles mutated) and 5697 (eIF4G alleles mutated in the A and/or D genome) were challenged with WSMV isolate ‘Sidney 81’. Expression levels of the targeted genes in edited-lines were reduced, compared to control Bobwhite_wild-type. However, characteristic WSMV symptoms developed both in edited-lines and in Bobwhite_wild-type, and differences in virus accumulation were not found, suggesting that the knockout of these genes had no effect on virus infection. Implementation of new CRISPR-based genome editing technologies should be considered to introduce resistance to these diseases in wheat.
Keywords: Genetic transformation of wheat; CRISPR/Cas9-mediated gene editing; Fusarium head blight; Wheat blast; Wheat streak mosaic virus